PENGARUH PELATIHAN TERHADAP KINERJA PEGAWAI INSTALASI RAWAT INAP TERPADU B RUMAH SAKIT UMUM PUSAT (RSUP) H. ADAM MALIK MEDAN - Yessy Refalina Van Sagala; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the effect of training on employee performance in the Integrated Inpatient Installation B of Adam Malik Hajj Center General Hospital, Medan. This research is an associative research. The population in this study consisted of 131 employees of Installation Rindu B. The number of samples is 36 respondents with the sampling technique is proportional stratified random sampling. Data collection techniques in this study used questionnaires and documentation. The analysis technique used is descriptive analysis. This research was conducted using the theory of Employee Training and Performance. The conclusion from this study is that there is a fairly strong effect of training on the performance of employees of Rindu B Installation at the Adam Malik Hajj Center General Hospital in Medan. This shows that the better the training given to employees, the better the performance produced by employees of the Integrated Inpatient Installation B at the H. Adam Malik Central General Hospital Medan, and vice versa. Keywords: Training, Employee Performance